Aspectos ecológicos e biológicos de esponjas e de ascídias da região entre-marés da praia do Cabo Branco, João Pessoa, Paraíba, Brasil. - Gama, Petrônio Bezerra (2003)
Species of sponges and ascidians were studied with respect to frequency of their occurrence, zonation, recruitment, growth, and some other aspects related to colonization of substratum, in the intertidal zone of the Cabo Branco beach, in João Pessoa, State of Paraiba, Northeast Brazil, aiming the knowledge of the biology and ecology of those marine species. The benthic seafloor of the intertidal borderlines zones was characterized in three transects perpendicular to the water line, based on different levels of spring tides, which were subdivided in three distinct zones: supralittoral, mesolittoral/ littoral, and sublittoral. The mesolittoral zone was subdivided in three subzones: upper, middle, and lower. The topographical profile of the beach was analysed on the transects, by configuring the arrangement and distribution of the rocky substratum of the abrasion platform, the extension of the different zones and subzones, and the soil declivity. The frequency of occurrence of sponges and ascidians in two transects was estimated throughout one year by observing the sea- and continent-facing rocks, along a 10m long stripe per transect, which showed that: (a) the sponges Tedania ignis, Cliona sp, Halichondria sp, Haliclona sp, Ircinia sp, and the colonial ascidians Didemnum duplicatum, Didemnum psamathodes Eudistoma sp1, Polysyncraton amethysteum and Symplegma rubra occur significantly in the lower mesolittoral, but D. duplicatum and D. psammathodes may occur up to the initial part of the middle mesolittoral; (b) with exception of Haliclona sp, all the species of sponges and ascidians are distributed indistinctly on both sea- and continent-facing rocks. A zonation proposal is presented including adjoining molluscans and crustaceans species to the sponges and ascidians here studied. The recruitment of ascidians and sponges was estimated throughout one year on four sea- and continent-facing scraped off rocks, located in the lower mesolittoral, which showed that: (a) the sponges showed three periods of recruitment; (b) the ascidians showed an annual recruitment; (c) recruitment differed on each face of the rocks; (d) abiotic factors affect the recruits survival; (e) there is a species-dependent differential mortality of the recruits. The seasonal growth of D. psammathodes was analysed from specimens recruited from scraped rocks of the lower mesolittoral, which showed that: (a) after a rapid initial growth, the colony continues growing more slowly, then senesces and dies; (b) life span of colonies varies from three to nine months depending upon the season of the year; (c) the daily growth rate is season-dependent and may generate a maximum value of 8.52cm2 day-1; (d) biomass is related to the colony area; (e) the highest value of area growth noted was 275.37cm2. Colonization of the scraped off natural substratum is gradual and it depends on the reproduction period of the species, and on abiotic conditions. Colonization involves successive recruitment and young mortality events. One year afterwards, the new community of sponges and ascidians did not have the same development as the remaining communities on untouched rocks.